[10] Digital rectal examination: is it essential for the screening of prostate cancer - Samir Bouras (Taylor & Francis Group, 2018)
Objective: To investigate the place of digital rectal examination (DRE) in the practice of general practitioners (GP) in our region (primary care physicians), as historically there have been two ways to screen for prostate cancer: DRE and prostate-specific antigen testing. Methods: This is a descriptive cross-sectional evaluation of practices, in a declarative and anonymous mode. The survey was conducted based on a pre-established questionnaire with 145 GPs in the public and private sector, in the region. The questionnaire included three components: identity criteria of physicians, the diagnosis approach of low urinary tract symptoms (LUTS), and their theoretical knowledge of recommendations including screening. Results: In all, 137 (94%) GPs participated in this study, including 70 (51%) men and 67 (49%) women. The mean (range) age was 44.6 (25–72) years. DRE was considered to be recommended by 116 (86.6%) GPs; however, it was only performed in a systematic way by five (4%), including one woman. In all, 76 GPs (55%) said they had done it systematically at the beginning of their exercise. Male GPs did more DREs vs female GPs, at 39 (56%) vs 14 (21%), and this difference was statistically significant (P < 0.001, odds ratio 4.7). Only 28 GPs (28.4%) thought that the DRE should be performed by a urologist; and 38 female GPs (67.9%) reported that their gender was a barrier to this test. Nine women reported a refusal of DRE because of their sex. Conclusion: Although it is true that the recommendations are not very clear concerning screening, the fact remains that many GPs do not follow any of them. Knowing the value of DRE, many of them do not realise it and do not refer to a urologist. This ambiguous diagnosis approach requires better organising of consultations and emphasises the need to strengthen practitioners’ knowledge of screening in general.